The Relationship of Serial Storytelling Activities in Stimulating Early Reading Ability in Kindergarten - Liswatun Hasanah; Dian Nita Dwi Puspita; Ida Aminatazzuhriyah; Iftitah Hanif N (Universitas Negeri Makassar, 2022)
The purpose of the study was to find out how storytelling activities relate to using series image media in improving initial reading skills. The formulation of the problem stated in this study is the low initial reading ability in children of Al-Karomah Kindergarten PGRI 4 Pujon. The type of research used is quantitative, using a correlation approach. The subject to be studied is a child, which amounts to 15 children. The required data collected through observation sheets, documentation, and data acquisition of relationships of two or more variables will be analyzed using descriptive and inferential statistics. The coefficient results obtained from the regression test analysis showed that the constant value was 1.975. In contrast, the serialized image storytelling value received a value of 0.902, so the regression model equation above can be described as Y = a + bX or 1.957 + 0.902X. Following the results described, it can be concluded that there is a significant relationship between serial drawing storytelling activities and children's initial reading ability.